Personalized Genetic Testing and Norovirus Susceptibility - Natalie Prystajecky; Fiona SL Brinkman; Brian Auk; Judith L Isaac-Renton; Patrick Tang (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: The availability of direct-to-consumer personalized genetic testing has enabled the public to access and interpret their own genetic information. Various genetic traits can be determined including resistance to norovirus through a nonsense mutation (G428A) in the FUT2 gene. Although this trait is believed to confer resistance to the most dominant norovirus genotype (GII.4), the spectrum of resistance to other norovirus strains is unknown. The present report describes a cluster of symptomatic norovirus GI.6 infection in a family identified to have norovirus resistance through personalized genetic testing.